The Mediating Roles Of Sustainable Tourism Practices Among Tour Operators - Abdul Hamid, Maisarah (2019)
Tourism businesses are encouraged to be involved in sustainability in order to gain a competitive advantage for them. Tour operators, as the entities of intermediaries between suppliers and customers, are required to be involved in the sustainable tourism sector. Their involvement is highly required for guaranteeing both business and destination sustainability. A plethora of research has discussed about organisational resources that influence their business performances. However, there are limited studies on sustainability, particularly from tour operators‘ perspectives. The aim of this research is to examine organisational resources and their sustainable practices towards the tour operators‘ performances.